“Structural and Modal Analysis of Quadcopter Frame: Material Optimization for Load-Bearing Efficiency” - Avinash Somatkar, Mukund Kharde, Vishwanath Mali, Shashikant Thakare, Bhausaheb Dane, Vijay Bhambere (The International Journal of Multiphysics, 2024)
Unmanned Aerial Vehicles (UAV), due to the ability of carrying huge payload, have wide applications from military surveillance, medicinal supply to agricultural purposes. To fulfil these applications effectively, the body frame of quadcopter must be able to withstand the various loading conditions. The present study deals with the structural analysis of a quadcopter frame to study the effect of specified loading conditions on the body frame. Further modal analysis was done for material optimization. Four different materials were selected which includes Aluminium alloy, Copper alloy, Carbon fibre, E-glass fibre. From modal analysis six modes with respective frequencies for all four materials were obtained. Based on the results, suitable material was selected which will suit the specified loading conditions.